Nurses’ perception about risk classification in an emergency service - Cristiane Chaves de Souza (Investigación y Educación en Enfermería, 2014)
Objective. Get to know how nurses perceive the accomplishment of risk classification in an emergency service. Methodology. In this qualitative study, 11 nurses were included with at least two months of experience in the risk classification of patients who visited the emergency service. Semistructured interviews were used to collect the information. The data were collected between August and December 2011. For data analysis, Bardin’s theoretical framework was used. Results. The nurses in the study consider the risk classification as a work organization instruments that permits closer contact between nurses and patients. The nursing skills needed for risk classification were identified: knowledge about the scale used, clinical perspective, patience and agility. The availability of risk classification scales was the main facilitator of this work. The main difficulties were the disorganization of the care network and the health team’s lack of knowledge of the protocol. Conclusion. Risk classification offers an opportunity for professional autonomy to the extent that it is the main responsible for regulating care at the entry door of the emergency services.